Peran Lingkungan Kerja Non Fisik dan Sistem Reward Terhadap Kinerja Trainee Generasi Z di Bagian Pastry and Bakery Hotel BCR Surabaya - Syafitri, Novriadila; Purwidiani, Niken; Sutiadiningsih, Any; Widagdo, Andika Kuncoro (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the role of non-physical work environment, reward system and the interaction between non-physical work environment and reward system on the performance of Gen Z Trainees in the Pastry and Bakery Section of Hotel BCR Surabaya. This type of research is quantitative research, with an associative method. The data used are primary data obtained from respondents through distributing questionnaires to 30 trainees. The data analysis techniques used are multiple linear regression analysis, classical assumption test, and hypothesis test. The results of the study show that: 1). Non-physical work environment has a significant effect on trainee performance, with a significance value of 0.000 and a t-count of 5.242. 2). The reward system does not show a significant effect on trainee performance, with a significance value of 0.111, and 3). there is a significant interaction between non-physical work environment and reward system in improving trainee performance, with an F-count value of 26.740 and an R2 value of 0.815 or 81.5%, affecting trainee performance while the remaining 18.5% is influenced by other variables not included in this model